A Study of the effect of Dexamethasone on the lung development and external morphology features during early embryonic stages in the swiss albino mice embryos Mus masculus - Naeem Salman, Ali; Ghaleb Taher Al- Musawi, Sada (University of Thi-Qar Journal of Science, 2017)
This study include the investigative the effect of Dexamethasone on the lung development and External morphology features at early Embryonic Developmental stages and evaluate Alpha Fetoprotein levels .Sixty pregnant mice were randomly divided into four groups and each group include 15 pregnant mice. Given the members of each group specific dose of (Dex) and at different time periods, while the control group injected with a solution of Normal Saline 0.9%, all animals received doses used by tail intravenous injection. In the end of specific period of pregnancy embryos were isolated from mothers ,mother’s blood were taken to evaluate AFP levels .The results of statistical analysis at (P < 0.05) to different doses Dexamethasone show there a negative effects on mice embryo’s body weights and the lengths increase with increasing of number and doses concentrations, (Dex) also affected on general external morphological features in embryos and on their lung development ,Dex has been affected on the lung development through lung cell proliferation and activity, especially at long terms and repeated doses.It’s has been caused congenital malformations in embryos: Death of embryos ,placenta damage ,neural Tube Defect ,Trunk Torsion ,Head hemorrhage, Brain hypertrophy ,Liver Hypertrophy ,Letter C Shape Embryos, swelling ,Convoluted Tail ,Short limbs.The Altered in the AFP levels have been observed concurred with aberrant growth manifestations .